Modelling Thought Processes on a Neural Network - Ranatunga, L. P. (Malaysian Journal of Computer Science, 1997)
The analysis and classification of consciousness and the details of human thought processes can be found in the Theravada Buddhist theory of mind. A thought process consists of several thought moments and each thought moment has some sort of function in the process. The constituents of thought moments, known as mental states, can be computed. Based on such a computation, we construct a neural network to model thought processes.